Simulation Validation for Thermal Performance of Building Envelope Material in Humid Tropical Higland Climate - Huda Dawam Indana; Asri Dinapradipta; Fransiskus Xaverius Teddy Badai Samodra (IPTEK Journal of Proceedings Series, 2020)
Modeling and simulation using computer software are very important in supporting various types of research based on data calculations. In the research process, accuracy is needed between the simulation results and the results of field measurements. Thus, there is no significant difference between the two results. This study aims to verify and validate the result of field measurements and simulation using the ARCHIPAK 5.1 software. The variables studied focus on indoor air temperature and humidity. This research takes a case study in the village of Ranupane which is located within the Bromo Tengger Semeru National Park. There are 4 housing buildings measured which consist of two types of houses using fireplaces and two types of houses without fireplaces. All of the four houses are afterward modeled using the ARCHIPAK 5.1 software to validate the data results. From the measurement results, the field measurement data show a higher hourly temperature profile compared to the results of the simulation of the base case model. Two striking differences are the type of house without a fireplace which is showing the difference in the average temperature of 1-2 K. While the type of house using fireplace shows the difference average temperature of 5,2-5,3 K. This occurs due to the internal heat gain input which the value is a slight difference between the result of field measurements and simulation of the base case model. This data verification and validation will be used as modeling optimal building configuration for housing in a humid tropical highland climate.